(3fHPI ef TYQ CHj GdeQJVi YHOGdMSjf Hf CMeO Bd TcQ GdfLaj GdYdhis ((3eMeO GdSeGhj s)
(3ChdgG (B:s
(3bGd GdTjN YHOGdMSjf QGKjkG CejQ GdeDefjf Ydi Hf CHj WGdH eG ddUhGQe adJ ef Hf neVQ gd Gdfhi UGQe GdbOQ s
(3BNQgG (B:s
(3hJdc JTch bjOkG gOGdYXGe hPi CHGgG JfYi dgai HCdLGf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B127 s
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B- (3GdfLa (B(1090) s
Keywords: (3GdCOHs